The role of interindividual licking received and dopamine genotype on later‐life licking provisioning in female rat offspring. Issue 4 (9th February 2021) - Lauby, Samantha C.; Ashbrook, David G.; Malik, Hannan R.; Chatterjee, Diptendu; Pan, Pauline; Fleming, Alison S.; McGowan, Patrick O.
Abstract: Introduction: Rat mothers exhibit natural variations in care that propagate between generations of female offspring. However, there is limited information on genetic variation that could influence this propagation. Methods: We assessed early‐life maternal care received by individual female rat offspring, later‐life maternal care provisioning, and dopaminergic activity in the maternal brain in relation to naturally occurring genetic polymorphisms linked to the dopaminergic system. We also conducted a systematic analysis of other genetic variants potentially related to maternal behavior in our Long‐Evans rat population. Results: While we did not find a direct relationship between early‐life licking received and later‐life licking provisioning, this relationship was indirectly affected by dopamine levels in the nucleus accumbens and dependent on variation in the dopamine receptor 2 gene (rs107017253). More specifically, female rat offspring with the A/G genotype showed a positive relationship between average licking received and dopamine levels in the nucleus accumbens of the maternal brain; there was no relationship with female rat offspring with the A/A genotype. The higher dopamine levels in the nucleus accumbens corresponded with higher maternal licking provisioning from postnatal days 2–9. We also discovered and validated several new variants that were predicted by our systematic analysis. Conclusion: Our findings suggest that genetic variation influences the relationship between early‐life maternal care received and the dopaminergic system of the maternal brain, which can indirectly influence later‐life maternal care provisioning. Abstract : Rat mothers exhibit natural variations in care that propagate between generations of female offspring, but there is limited information on genetic variation that influences this propagation. We assessed early‐life maternal care received by individual female rat offspring in relation to genetic polymorphisms linked to dopaminergic activity, maternal care provisioning, and dopaminergic activity in the maternal brain. We found that dopamine receptor 2 (rs107017253) variation interacted with the relationship between early‐life maternal care received and dopamine levels in the nucleus accumbens which, in turn, were associated with later‐life maternal care provisioning.